Effectiveness of tobacco control television advertisements with different types of emotional content on tobacco use in England, 2004–2010 - Sims, Michelle; Langley, Tessa; Lewis, Sarah; Richardson, Sol; Szatkowski, Lisa; McNeill, Ann; Gilmore, Anna B. (BMJ Publishing Group, 2014)
Aim: To examine the effects of tobacco control television advertisements with positive and negative emotional content on adult smoking prevalence and cigarette consumption.